Peculiarities of the Relationship between Immunological Parameters and Endothelial Dysfunction in Patients with Bronchial Asthma, Chronic Obstructive Pulmonary Disease and Their Combination (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
To date, many studies have defined COPD-bronchial asthma crossover syndrome as a phenotype of COPD. Patients with a cross between bronchial asthma and chronic obstructive pulmonary disease (COPD) have differences with patients with isolated bronchial asthma (BA) and chronic obstructive pulmonary disease (COPD). Separation of such patients into a special group seems to be justified and appropriate from the standpoint of pathophysiology, clinic and therapy.